Pra-Pernikahan Rasulullah, Komunikasi Dakwah Dalam Konteks Budaya - Musrifah (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2020)
In Islam, marriage is a form of worship with a clear set of rules. Arranged in Al Quran, exemplified in As Sunnah. As a human being, the Prophet Muhammad was married. Even getting married is one of the sunnah. The interesting question is how was the marriage of the Prophet Muhammad before he was sent to be a prophet and the marriage after the birth of the Islamic message? This article was written in order to answer the question of how the Prophet Muhammad's marriage before and after becoming a prophet and apostle was seen from the perspective of da'wah communication in a cultural context. Through analysis of the sirah nabawi and various other scientific literacies, the author can conclude that there is a strategic role for da'wah communication in the marriage of the Prophet Muhammad before and after he became a prophet and apostle. The role of da'wah communication is actually very dominant in pre-wedding or pre-wedding processions. And the communication of da'wah carried out by the Prophet Muhammad was not common in the Arab culture at that time. However, we can see how smart the Prophet Muhammad was in introducing pre-wedding culture through his preaching communication.